Usage, History, Systematics, Morphology and Chicpea (Cicer Arietinum L.) Varieties Grown In Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article provides a comprehensive overview of chickpea (Cicer arietinum L.), focusing on its usage, historical significance, botanical classification, morphological characteristics, and the main varieties cultivated in Uzbekistan. The paper highlights chickpea’s role as a vital leguminous crop with nutritional, agronomic, and economic importance. A review of its domestication history traces its origin to the Fertile Crescent and its subsequent spread to Central Asia. The article explores the systematic placement of the species within the Fabaceae family and describes key morphological features such as seed shape, leaf structure, flowering pattern, and root system. Special attention is given to chickpea varieties adapted to the agro-climatic conditions of Uzbekistan, including local breeding efforts and productivity traits. The study aims to support the conservation, breeding, and sustainable development of chickpea cultivation in the region by compiling critical scientific and agronomic insights.